Brokers and brokerage in the process of trading in commodity futures markets - Eremić Milan B. (Ekonomski Anali, 2003)
This paper mainly deals with the analysis of a very complex process of brokerage in commodity futures markets. Unlike a classical commodity market in which brokers are not a necessity, sales and purchases in commodity futures markets cannot be carried out without brokers. Brokers who act as agents of buyers and sellers of futures are a necessary condition for trading in organized markets, such as commodity futures markets. The structure of brokers in futures trading is multilayer and involves participants in futures trading from floor brokers, immediate futures traders and the members of clearing and the clearing house itself, on the one hand, to numerous other necessary actors whose activities out of the stock exchange and the clearing house contribute to the efficient functioning of futures market. The fact that transactions between buyers and sellers in futures markets are not carried out directly but through brokers means that the obligations of buyers and sellers are formally conveyed to brokers, providing at the same time the guarantee by the broker that the actual buyer and the actual seller will fulfill their contractual obligations. At the very beginning of futures trading, the relationship between the seller and the buyer is transformed into a relationship between two brokers. Since that moment on, the original relationship is conveyed to higher levels of brokerage reaching the level of the clearing house. In the process of transformation of the buyer-seller relationship and transmitting obligations and guaranteeing their fulfillment, the clearing house itself becomes the buyer relative to all sellers and the seller relative to all buyers. In this way, it guarantees that obligations regarding all transactions in futures market will be fulfilled. The whole process is carried out in accordance with the prescribed procedures conducted on the floor of commodity exchange, in its administrative departments and in the clearing house itself.